2015
DOI: 10.24114/inpafi.v3i2.5134
|View full text |Cite
|
Sign up to set email alerts
|

Efek Model Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Siswa Pada Materi Listrik Dinamis Di Kelas X Semester Ii Sma Negeri 1 Hinai Kabupaten Langkat T.A. 2013/2014

Abstract: ABSTRAK Penelitian ini bertujuan untuk mengetahui  apakah hasil belajar dengan menggunakan model pembelajaran berbasis masalah lebih baik daripada pembelajaran konvensional pada materi Listrik Dinamis di kelas X Semester II di SMAN 1 Hinai Kabupaten Langkat T.A. 2013/2014.Jenis penelitian ini adalah quasi experiment. Populasi dalam penelitian ini adalah seluruh siswa kelas X Semester ganjil SMAN 1 Hinai yang terdiri dari empat kelas. Sampel penelitian ini diambil dua kelas yaitu kelas X-1(sebagai kelas ekspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The last skill of the 4C is communication. Communication skills include the ability to express thoughts clearly and persuasively, both orally and in writing, articulate opinions, communicate coherent instructions and motivate others through speech [9] [10]. Effective communication skills can help avoid misunderstandings and miscommunication.…”
Section: Introductionmentioning
confidence: 99%
“…The last skill of the 4C is communication. Communication skills include the ability to express thoughts clearly and persuasively, both orally and in writing, articulate opinions, communicate coherent instructions and motivate others through speech [9] [10]. Effective communication skills can help avoid misunderstandings and miscommunication.…”
Section: Introductionmentioning
confidence: 99%
“…Through research journals such as those conducted by [5], [6], [7], [8] stated that the problem-based learning model positively impacts problem-solving skills, and student learning outcomes. Meanwhile, according to [9] that problem-based learning model can improve students' critical thinking skills and [10], [11] stated that the problem-based learning model can increase students' critical thinking skills and problemsolving skills.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the positive impact of the implementation of problem based learning models, they are [10], [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%